PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN KEBIJAKAN PERUSAHAAN TERHADAP KINERJA KEUANGAN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT PT NUSANTARA SEBELAS MEDIKA - Priandari, Sri; Riyadi, Slamet; Ingga, Ibrahim (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
The purpose of this research is to analyze and interpret the influence of HR Quality and company policy on competitive advantage and financial performance. The population in this study were 60 employees of PT Nusantara Sebelas Medika. In this study the sampling used a saturated sampling technique. Saturated sampling is the determination of the sample if the sample population is used. This is often done if the population is relatively small, fewer than 30 people, or research that wants to generalize with very little errors. Another term saturated sampling is a census, where all members of the population are used as samples. From this understanding the maximum number of samples is equal to the number of population, namely a number of 60 employees of PT Nusantara Sebelas Medika by using PLS SEM data analysis as an analysis of hypothesis verification. The results in this study give the meaning that the quality of HR and company policies have a significant effect on competitive advantage and financial performance and competitive advantage have a significant effect on financial performance.